Sense and Sustainability - Hickson, Ken (Institutional Knowledge at Singapore Management University, 2012)
Like the proverbial chicken and egg, climate change and sustainability are inextricably linked; it is impossible to decide which comes first, but urgent solutions are needed. Ken Hickson delivers a timely lesson on the four E’s of sustainability—energy, environment, economics and ethics.